Pre- and post- COVID-19 comparative stock return analysis on specific industries in Dhaka Stock Exchange - Yasar, Samin (Brac University, 2022)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2021.